ANALYSIS OF SUMATERA QUARTZ SAND AND SURROUNDINGS AS FRAC SAND AND IDENTIFICATION OF MAIN PARAMETERS DETERMINING CRUSH RESISTANCE - Mahdya Ananda, Indah
To increase reservoir production, especially in non-conventional systems, proppant has an important role in hydraulic fracturing techniques to hold fractures open. Among the various types of proppants, natural quartz sand, called as frac sand, has not been utilized optimally in Indonesia, even though the resource potential is quite large. This research is divided into three stages of activities: introduction, data collection and processing, and data analysis. The intoduction stage includes a literature study regarding proppants, especially frac sand, and geological conditions of the study area. The data collection and processing stage consists of quartz sand sampling and testing samples in the laboratory. Laboratory analysis includes analysis of sieve, roundness, sphericity, acid solubility, turbidity, bulk density, absolute density, and crush resistance. The data analysis stage includes assessing quartz sand quality as frac sand in accordance with API Standard 19C (2018), identifying the main parameters determining crush resistance quality, and evaluating quartz sand quality against geological conditions. The results of the sieve analysis showed that samples were dominated by grain size fractions 30/50 and 40/70. Binocular microscope observations show roundness values 0.35 - 0.65 and sphericity values 0.55 - 0.63. Acid solubility analysis shows a percentage value of dissolved material of 0.45 – 7.93%. Turbidity analysis shows that the samples generally have turbidity values of 217 – 18,450 FTU. Overall, the samples have absolute density values around 2.65 - 2.69 and these are close to quartz density, while the bulk density ranges between 1.34 - 1.60. Based on assessments referring to API Standard 19C (2018), there are no samples that meet the criteria for frac sand. Based on Pearson correlation analysis, the sphericity parameter has the strongest influence with a correlation value of -0.73, then the roundness parameter with a correlation value of -0.63. Based on regional geological approach, it can be concluded that quartz sand that has experienced multi-cycle sedimentation has relatively better textural maturity and will improve its quality as frac sand.